An analysis of the "Gallery of the Mind" - Carino, Leonardo Rey Salazar; Florendo, Raquel Baltazar (1991.)
(no abstract provided by the author)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Abueva, Napoleon Veloso, 1930-.; Chapels -- Philippines; Church architecture -- Philippines